Copyright Protection By The Collective Management Organizations in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article deals with the issues of ensuring the protection of copyright objects when using them in telecommunication networks. In particular, the role of blocking means in this direction, methods and technical requirements for protection, as well as the processes of regulation of legal relations in this direction are described. In addition, the article describes the world experience in this direction, the role of the “Internet contracts” of the WIPO, technical means of protecting copyright on the Internet, as well as the norms and practice of the legislation of Uzbekistan.